Overview of Mother`S Body Mass Index (BMI) Before Pregnancy, Weight Gain, Upper Arm Circumference, and Hemoglobin Levels During Pregnancy, and Baby Birth Weight at The Cilandak District Health Center - Harjatmo, Titus Priyo; Wanda Yulieta, Tasyafia; Syarief Darmawan, Syarief; Wiyono, Sugeng; Nareswara, Anastu Regita; Nugroho, Alfiantani (Politeknik Kesehatan Kemenkes Jakarta II, 2023)
Pregnancy is a critical period that determines the quality of human resources in the future. The growth and development of children are largely influenced by the condition of the fetus in the womb. The fetus's growth can be influenced by the mother's nutritional status before and during pregnancy. A healthy and normal weight baby is likely to be born to a mother with a normal nutritional status before and during pregnancy. Therefore, strategic efforts are needed during the pre-pregnancy and pregnancy period to create a healthy and resilient generation. The mother's nutritional status before pregnancy can be determined by her body mass index (BMI), while the nutritional status during pregnancy can be evaluated based on weight gain, upper arm circumference, and hemoglobin levels. The purpose of this study is to describe the mother's BMI before pregnancy, weight gain, upper arm circumference, and hemoglobin levels during pregnancy, and birth weight at the Cilandak District Health Center. This research is descriptive and based on secondary data from the Cilandak District Health Center, with a cross-sectional research design. The results show that pregnant women with very low and low BMI before pregnancy had a higher proportion of Low Birth Weight (LBW) infants (60%). Pregnant women who did not gain weight up to the standard during pregnancy also had a higher proportion of LBW infants (55.8%). Pregnant women with chronic lack of energy based on upper arm circumference measurements had a higher proportion of LBW infants (71.4%). Additionally, pregnant women with non-anemic hemoglobin levels also had a higher proportion of LBW infants (54.3%). Overall, this study highlights the importance of maintaining a healthy nutritional status before and during pregnancy to promote the birth of healthy and normal weight babies. Further research may be needed to investigate the factors that affect maternal nutritional status during pregnancy and identify interventions that can be implemented to improve maternal and fetal health outcomes. Keywords: Body Mass Index (BMI), Upper Arm Circumference, Hemoglobin Level, Baby Birth Weight